2018
DOI: 10.1038/s41467-018-05863-5
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the biexciton and trion-exciton complexes in BN encapsulated WSe2

Abstract: Strong Coulomb interactions in single-layer transition metal dichalcogenides (TMDs) result in the emergence of strongly bound excitons, trions, and biexcitons. These excitonic complexes possess the valley degree of freedom, which can be exploited for quantum optoelectronics. However, in contrast to the good understanding of the exciton and trion properties, the binding energy of the biexciton remains elusive, with theoretical calculations and experimental studies reporting discrepant results. In this work, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
230
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 237 publications
(260 citation statements)
references
References 60 publications
28
230
2
Order By: Relevance
“…28,33 . As a result, we previously found that the valley-resolved PL spectra under an out-of-plane magnetic field exhibit a unique "cross" pattern in the intrinsic regime, distinctively different from other excitonic complexes [29][30][31] . Here we apply magneto-PL spectroscopy to investigate a topgated monolayer WSe2 device and found a similar pattern in the n-or p-doped WSe2.…”
Section: Main Textmentioning
confidence: 95%
See 1 more Smart Citation
“…28,33 . As a result, we previously found that the valley-resolved PL spectra under an out-of-plane magnetic field exhibit a unique "cross" pattern in the intrinsic regime, distinctively different from other excitonic complexes [29][30][31] . Here we apply magneto-PL spectroscopy to investigate a topgated monolayer WSe2 device and found a similar pattern in the n-or p-doped WSe2.…”
Section: Main Textmentioning
confidence: 95%
“…1d). As a result, in a non-interacting picture in which the Zeeman splitting is calculated through the individual shift of CBM and VBM associated with the recombination electron-hole pair 29,47 , the magneto-PL spectra of X D + and X D − will share the same Zeeman splitting as the charge-neutral X D . Therefore, we assign the emerging "cross" patterns in the hole-doped and electron-doped WSe2 ( Fig.…”
Section: Main Textmentioning
confidence: 99%
“…S1. Monolayer WSe2 hosts a rich spectrum of excitonic species [23][24][25][26][27][28] . Several previously identified excitonic states are indicated in the figure, including the neutral bright exciton ( 0 ), bright trions ( ± ) [29][30][31][32][33] , the intravalley spinforbidden dark exciton ( 0 ) 17-20, 34 , and dark trions ( ± ) 18, 35 .…”
Section: Maintextmentioning
confidence: 99%
“…Finally, we transferred another few-layer graphene flake to work as the top-gate electrode, on top of the top h-BN flake. 26,27 We applied a confocal micro-PL setup to measure the magneto-PL with the out-of-plane magnetic field. A linear polarized light is converted into circularly polarized light by a quarter waveplate and the laser is focused by a 50X objective (NA: ~ 0.65) to excite the WSe2 sample, with the spot size of ~ 2 μm.…”
Section: Fabrication Of H-bn Encapsulated Monolayer Wse2 Devicementioning
confidence: 99%